KARAKTERISTIK KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VIII DI KABUPATEN BANDUNG BARAT - Pujiyanti Sahri; Jozua Sabandar; Aflich Yusnita Fitrianna (IKIP Siliwangi, 2023)
This study aims to determine the characteristics of the problem solving abilities of class VIII students in a junior high school in West Bandung Regency. In this study using a qualitative descriptive research method. The data collection technique in this study was in the form of test questions. The test results were analyzed by the emergence of problem solving abilities based on the Polya procedure for each question. The test instrument used is a description test. Based on data analysis of the study found that the stages of solving problems obtained 87% results, and at the other 3 stages namely understanding the problem obtained 55% results, planning problem solving obtained 30% results and checking again obtained 20 results %. Thus, there are still many students who do not write down what is known, are asked, and do not describe these elements, are not systematic in the problem solving process, do not understand the problem, are wrong in calculating answers, and do not write conclusions, and the main factor is not students are used to solving problems in the form of stories with complex daily life contexts, so there are still many errors in problem solving systematics found in junior high school students.